Investigating Brand Loyalty Factors among Young Mobile Phone Users - Mohd Noor Azam, Ayob (2010)
One of the key elements in marketing mix is to successfully promote and build a brand name for business to progress. Hence, this study is to investigate Brand Loyalty factors among young mobile phone users in the Mobile Telecommunication Sector in Malaysia. In this research, five antecedents of customer satisfaction that leads to customer loyalty are identified. The variables measured are "Switching Cost", "Corporate Image", "Service Quality", "Trust" and "Promotion". A total of 400 questionnaires were distributed to three schools in Bukit Mertajam, Pulau Pinang. 337 questionnaires were returned and useable representing 84.3 percent response rate. The Pearson correlations test that was conducted showed that "Promotion" is the highest influential factor in influencing brand loyalty in mobile telecommunication sector. This is followed by "Trust", "Service Quality", "Corporate Image" and "Switching Cost". The findings although might be premature since it was conducted in a small scale. However, it could have prescribed potential implications for mobile telecommunication service providers to review their loyalty programs to retain existing customers and at the same time attract new ones.